The impact of the Okavango River on the health of the community of Sepopa Village in the Okavango District, Botswana - Mosarwana, Ketlabareng Peaceful (My University, 2015)
Introduction: A qualitative study was undertaken to assess the impact that flooding of the Okavango river have on the health of the community of Sepopa village. Aim: To assess the impact that flooding of the Okavango River has on the health of the community of Sepopa village. Study: the study was conducted in the village of Sepopa within the community aged between fifteen years and above. The village has an estimated population of 2824. Method: A non experimental descriptive research design using qualitative approach was used. Sampling: Two types of sampling procedure were used, being simple random sampling and purposive sampling. Results: The study revealed that 85% of the respondents reported or suffered from the injuries due to high waters brought about by floods, 92% reported to have fallen sick or having a member of their family who was sick with conditions related to floods. Of all the respondents, 54% explained they heard of deaths occurring in a river either due to drowning or crocodile and hippopotamus attacks. Lastly, 8% of respondents reported they never heard of any injuries, illness or death due to the impacts of floods. Conclusion: It can thus be concluded that the river has an impact to the health of the community either before, during and after a flood event, activities may be undertaken by the population at risk, by policy makers and by emergency responders to reduce health risks. Proper planning aimed to reduce the harmful effects of flooding by limiting the impact of a flood on human health and economic infrastructure should be adopted. Key words: health, sepopa village, impact, Okavango river.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Flooding; Flooding and Health problems; Floods -- Botswana.; Floods -- Okavango River; Public health -- Botswana.